Converging Mainlander and Native Taiwanese, 1949–2012. (12th August 2016) - Hao, Yu
Abstract : This paper uses a surname‐based methodology to estimate the intergenerational correlation between native Taiwanese and mainlanders during 1949–2012. It finds that mainlanders, who initially had an advantage in higher education and high profile occupations, regressed towards population average at a relatively constant rate, which is much higher than suggested by previous studies. This paper argues that the difference either reflects a group‐level inequality because of the impacts of kinships and extended families, or it measures the intergenerational correlation of an unobservable variable, the true underlying social status, which is imperfectly correlated with income, education, or occupation at the individual level.